2014
DOI: 10.1111/aor.12354
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-Encapsulated Hemoglobin Enhances Chemotherapy to Suppress Metastasis in Mice

Abstract: Liposome-encapsulated hemoglobin with high O2 -affinity (P50 O2  = 10 mm Hg, h-LEH) was reported to enhance tumor radiosensitivity. We hypothesize that targeted O2 delivery to tumor hypoxia by h-LEH may also enhance chemotherapy to suppress tumor growth and metastasis in mice. Doxorubicin (DXR; 0.5 or 2 mg/kg i.p.) or S-1 (4 or 8 mg/kg orally) alone or in combination with h-LEH (5 mL/kg i.v.) was administered for 2 weeks to C57BL/6N mice inoculated with Lewis Lung Carcinoma (LLC) in the leg. After the 2-week t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…It has been our consistent observation that liposome‐encapsulated hemoglobin (LEH), specifically with high O 2 affinity ( h ‐LEH, P 50 O 2 = 8–17 mm Hg), has been associated with suppressed inflammation to promote wound healing , reduce damage after ischemia/reperfusion , and enhance antitumor therapies . Whereas LEH with low O 2 affinity ( l ‐LEH, P 50 O 2 = 40–50 mm Hg) was able to maintain O 2 delivery as a whole in rabbits under hemorrhagic shock, it was not associated with improved peripheral perfusion or extended survival .…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…It has been our consistent observation that liposome‐encapsulated hemoglobin (LEH), specifically with high O 2 affinity ( h ‐LEH, P 50 O 2 = 8–17 mm Hg), has been associated with suppressed inflammation to promote wound healing , reduce damage after ischemia/reperfusion , and enhance antitumor therapies . Whereas LEH with low O 2 affinity ( l ‐LEH, P 50 O 2 = 40–50 mm Hg) was able to maintain O 2 delivery as a whole in rabbits under hemorrhagic shock, it was not associated with improved peripheral perfusion or extended survival .…”
mentioning
confidence: 95%
“…Although AOC with high O 2 affinity promotes targeted O 2 delivery , subsequent mechanism(s) remained unclear. As a clue for clarifying the link between O 2 delivery to hypoxic cells and subsequent tamed inflammation, unique observations are presented in this issue regarding the presence of O 2 promoting degradation of hypoxia‐inducible factor 1‐alfa (HIF‐1α) by O 2 ‐dependent hydroxylation (Fig. A).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that this encapsulation strategy can increase plasma retention time. However, unwanted immune interactions may happen from the liposome capsule [9]. As a new strategy, microcapsulation of hemoglobin shed light over creating real artificial red cells including the essential enzymes that act for the reduction of ischemia reperfusion injury and solve problems associated with methaemoglobin formation [10].…”
Section: Liposome-encapsulated Haemoglobinmentioning
confidence: 99%
“…With advancements in science, many strategies to control Hb's natural vasoconstrictive potential are now available. Encapsulation, PEGylation, CO-saturation, S-nitrosylation, or incorporation of ATP and adenosine are only a few examples of the strategies being implemented by artificial oxygen carrier developers (7,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). These strategies are evolving, and more concepts are on the way.…”
mentioning
confidence: 99%